Women living with HIV and dual contraceptive use in Ethiopia: systematic review and meta-analysis - Asteray Ayenew (BMC, 2022)
Abstract Background Despite different preventive strategies that have been implemented in the country, the prevalence of HIV/AIDS is still significantly increasing in Ethiopia. The concurrence of HIV and unintended pregnancy makes the use of dual contraception a back bone for the simultaneous protection against HIV, and unintended pregnancy. As a result, this systematic review and meta-analysis aimed to assess the prevalence and associated factors of dual contraceptive use among women living with HIV in Ethiopia. Method We used databases; (PubMed, Google Scholar, EMBASE, Cochrane Library, African Online Journals, and Hinary), other gray and online repository accessed studies were searched using different search engines. For critical appraisal of studies Newcastle-Ottawa Quality Assessment Scale (NOS) was used. The analysis was done using STATA 11 software. The Cochran Q test and I2 test statistics were used to assess the heterogeneity. To detect publication bias funnel plot and Egger's test were used. The pooled prevalence of dual contraception use and the odds ratio (OR) with a 95% confidence interval was presented by using forest plots. Result Eleven studies were included in this review, with a total of 4083 women living with HIV in Ethiopia. The pooled prevalence of dual contraception use in Ethiopia was 34.08% (95%CI: 20.77-47.38). Having open partner discussion (OR = 3.96, 95%CI:2.3,6.8), provision of post test counseling (AOR = 4.38, 95%CI:2.93,6.54), disclosed HIV status to sexual partners (OR = 5.9, 95%CI:4.19,8.33), partner involvement in post-test counseling (OR = 3.52, 95%CI:2.37,5.23), and being on highly active antiretroviral therapy (HAART) (OR = 2.9, 95%CI:1.56,5.46) were the determinant factors of dual contraceptive use in Ethiopia. Conclusion The overall prevalence of dual contraceptive use among women living with HIV in Ethiopia was low. Having open partner discussion, provision of post-test counseling, disclosed HIV status to sexual partner, partner involvement in post-test counseling, and currently on highly active antiretroviral therapy (HAART) were the associated factors of dual contraceptive use. Therefore, efforts should be made to provide post-test counseling, and initiate partner involvement in post-test counseling. Moreover, promoting open partner discussion, counseling to disclose HIV status to their sexual partner and to start HAART will be helpful in enhancing the use of dual contraceptive method use.